Characterization, Behavior, and Risk Assessment of Polycyclic Aromatic Hydrocarbons (PAHs) in the Estuary Sediments - Ambade, Balram; Sethi, Shrikanta Shankar; Giri, Basant; Biswas, Jayanta Kumar; Bauddh, Kuldeep (Bulletin of environmental contamination and toxicology, 2022)
Polycyclic aromatic hydrocarbons (PAHs) are persistent toxic substances that have ubiquitous presence in water, air, soil, and sediment environments. The growth of PAH toxicities and related ecotoxicology risk in estuary sediment has a serious concern. Present study examined the PAHs concentration, sources, and ecological risk from selected sites in Subarnarekha River estuary (SRE) sediment deposits. The sum of toxic 16 PAHs was ranged from 36.8 to 670.8 ng/g (mean = 223.46 ± 196.35 ng/g). The total PAH concentration varied significantly among the sampling sites (range 511.3 ng/g to 233.8 ng/g) based on allochthonous contaminant loads. Among the 16 compounds, Phen had the highest concentration (40.18 ng/g), followed by Pye (31.86 ng/g), Flur (29.36 ng/g), and NA (19.33 ng/g). Most of the sampling sites contained abundant 3-ring and 4–5-ring PAHs. Based on diagnostic ratios and PCA analysis petroleum combustion, biomass, and coal-burning have been identified as the major sources. The PAHs had high mutagenic equivalent factor and toxic equivalent factor values posing great ecological threats and health risks.